Original articleSertraline and curcumin prevent stress-induced morphological changes of dendrites and neurons in the medial prefrontal cortex of rats - Noorafshan, Ali; Abdollahifar, Mohammad-Amin; Karbalay-Doust, Saied; Asadi-Golshan, Reza; Rashidian-Rashidabadi, Ali (Folia Neuropathologica, 2015)
Stress induces structural and behavioral impairments. The changes in dendrites and neurons are accompanied by impairments in the tasks mediated by the medial prefrontal cortex (mPFC). The present study was conducted to evaluate the structural changes of the dendrites and neurons of the mPFC after stress using stereological methods. In addition, the effects of a natural and a synthetic substance, i.e., curcumin and sertraline, were evaluated. The rats were divided into 7 groups: stress + distilled water, stress + olive oil, curcumin (100 mg/kg/day), sertraline (10 mg/kg/day), stress + curcumin, stress + sertraline, and control groups. The animals were submitted to chronic variable stress for 56 days. The results showed an average 15% reduction in the length of the dendrites per neuron in the mPFC after stress (p < 0.004). The total spine density was reduced by 50% in the stress (+ olive oil or + distilled water) groups in comparison with the control group (p < 0.01). The main reduction was seen in the thin and mushroom spines, while the stubby spines remained unchanged. Mean volume and surface area of the neurons were decreased by 14% and 10% on average in the stress (+ distilled water or + olive oil) rats in comparison to the control rats, respectively (p < 0.01). The data revealed that treatment of stressed rats with curcumin or sertraline can prevent the loss of spines and reduction of dendrite length, volume and surface area of the neurons. Sertraline and curcumin can prevent structural changes of the neurons and dendrites induced by stress in the mPFC of rats.